Physical Phenomena: A Perspective of Quran and Modern Physics (Al-Qamar, 2020)
Quran has emphasized on the thinking about different scientific phenomena of this universe in many verses. With the development science and technology, the truth described in the verses of the Quran has been revealed to the world. Different scientific facts of Physics and cosmology like expansion of universe, existence of black holes, gravitational waves etc. have been indicated in the Quran fourteen hundred years ago. The Quran give us concept about creation of this universe, about laws of nature, electromagnetic waves and black holes. The purpose of this paper is to explain the different physical phenomena from Qur’ānic perspective.
Keywords: Physical Phenomena; Quran; Modern physics